The Orthodontic-Periodontal Risk Assessment (OPRA) in developing Periodontal Disease - Marino Musilli; Sherry Lee; Mauro Farella; Guerino Paolantoni (Publymed, 2020)
Fifty percent of the adult population suffers from periodontal disease. Patients with Stage IV periodontal disease have altered physiological dental relationships such as masticatory dysfunction, secondary occlusal trauma, increased tooth mobility, bite collapse, tooth migration and flaring. Occlusal forces can alter and adversely affect the outcome of periodontal therapy, thus orthodontic treatment can be considered to re-store occlusal harmony as well as improve smile aesthetics. The objectives of this article were 1) to underline the possible factors involved in the relationship between systemic conditions and periodontal disease during orthodontic treatment in patients with periodontal issues; 2) to propose an Orthodontic-Periodontal Risk Assessment model (OPRA) to account for risk factors associated with orthodontic treatment, estimating their impact on periodontal health in susceptible patients.